2022
DOI: 10.1007/s10465-022-09356-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dance/Movement Therapy Intervention for Children with Intellectual Disability at an Early Childhood Special Education Preschool

Abstract: Children with intellectual disability (ID) often have deficits in gross motor skills and static and dynamic balance abilities, poor lower muscle strength, and an increased risk of serious falls. They also face difficulty in continuing physical activity programs due to cognitive impairment and easy loss of motivation. However, dance/movement therapy (DMT) has been found to help children with ID perform static and dynamic movements.This study aimed to assess the effectiveness of DMT group sessions for children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Our previous study on the effectiveness of DMT on 21 children with ID, aged 3–6 years, showed that static balance measured through the one‐leg stand test increased significantly after 10 DMT group sessions (Takahashi et al . 2022). However, because the measurement lacks objectivity, the findings need to be confirmed through objective measurement methods.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study on the effectiveness of DMT on 21 children with ID, aged 3–6 years, showed that static balance measured through the one‐leg stand test increased significantly after 10 DMT group sessions (Takahashi et al . 2022). However, because the measurement lacks objectivity, the findings need to be confirmed through objective measurement methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the second part of the systematic review, the following studies are reported regarding the effectiveness of dancetherapy protocols. Takahashi et al (2022) have outlined a dance-therapy protocol for 21 children with intellectual disabilities, ageing 3 to 6 years, carried out in a rehabilitation setting (control group: n.10 subjects; experimental group: n.11 subjects). After a cycle of 10 one-hour dance sessions, the HHD post-test registered an increase in the strength of the extensors of both knees for all 11 participants.…”
Section: Methodsmentioning
confidence: 99%